2014
DOI: 10.1186/1476-4598-13-118
|View full text |Cite
|
Sign up to set email alerts
|

Loss of miR-638 in vitro promotes cell invasion and a mesenchymal-like transition by influencing SOX2 expression in colorectal carcinoma cells

Abstract: BackgroundColorectal carcinoma (CRC) is a major cause of cancer mortality. The aberrant expression of several microRNAs is associated with CRC progression; however, the molecular mechanisms underlying this phenomenon are unclear.MethodsmiR-638 and SRY-box 2 (SOX2) expression levels were detected in 36 tumor samples and their adjacent, non-tumor tissues from patients with CRC, as well as in 4 CRC cell lines, using real-time quantitative RT-PCR (qRT-PCR). SOX2 expression levels were detected in 90 tumor samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 41 publications
3
50
1
Order By: Relevance
“…Co‐immunofluorescence staining of migrating cells further demonstrated the presence of vimentin‐positive but SOX2‐negative tumor cells at the migratory front, the amount of which was strongly increased by conditional silencing of SOX2. In contrast to our findings, SOX2 was identified to promote migration of tumor cells, although mostly in cancers of non‐squamous cell origin (Ma et al., 2014; Wang et al., 2014). Regarding HNSCC, Yang and colleagues reported an association between SOX2 expression and enhanced migration and invasion capacities of the laryngeal squamous cell carcinoma cell line Hep‐2 (Yang et al., 2014a,b).…”
Section: Discussioncontrasting
confidence: 99%
“…Co‐immunofluorescence staining of migrating cells further demonstrated the presence of vimentin‐positive but SOX2‐negative tumor cells at the migratory front, the amount of which was strongly increased by conditional silencing of SOX2. In contrast to our findings, SOX2 was identified to promote migration of tumor cells, although mostly in cancers of non‐squamous cell origin (Ma et al., 2014; Wang et al., 2014). Regarding HNSCC, Yang and colleagues reported an association between SOX2 expression and enhanced migration and invasion capacities of the laryngeal squamous cell carcinoma cell line Hep‐2 (Yang et al., 2014a,b).…”
Section: Discussioncontrasting
confidence: 99%
“…This result was in consistence with others. For instance, attenuated miR-638-SOX2 axis was reported to promote the invasion by inducing epithelialmesenchymal transition in non-small-cell lung cancer [21], colorectal carcinoma [36], hepatocellular carcinoma [22]. Remarkably, Vanner and Boumahdi et al revealed SOX2 was important in regulating cancer stem-like cells [30,37].…”
Section: Figure 5: Knockdown Of Sox2 Antagonized the Pro-invasion Andmentioning
confidence: 99%
“…Multiple miRNAs have been reported to be involved in the stemness maintenance. In the case of CRC, factors such as miR-200c, miR-638, and miR-371-5p have been reported to regulate SOX2induced CSC properties [16][17][18] . Several recent studies have demonstrated that stemness-associated genes, such as OCT4 and Klf4, are also implicated in modulating angiogenesis and VM 19,20 .…”
Section: Introductionmentioning
confidence: 99%